Comparing FAHP and FANP Methods in Locating Multi-storey Parking Sites Shiraz’s CBD - Alireza Dehghani; Ali Soltani (Alanya Üniversitesi, 2024)
The substantial rise in automobile ownership and expansion of metropolitan areas in recent decades, especially in emerging nations, has resulted in a severe shortage of parking spaces. This problem not only causes significant traffic congestion and an increase in accidents but also places a considerable financial burden on individuals and worsens air pollution. Despite extensive research on addressing the parking issue, there is still a notable deficiency in effective approaches for selecting the best locations for multi-story parking structures, particularly in major cities in Iran. Hence, acknowledging the significance of effective parking management in addressing these problems, This study aimed to provide a comprehensive framework for choosing parking locations in Shiraz's business district. This study combined the Analytic Hierarchy Process (AHP) and Analytic Network Process (ANP) with a Geographic Information System to make fuzzy multi-criteria decisions. To determine suitable locations, factors such as proximity to business hubs, key roads, land prices, population density, and construction feasibility were assessed. The findings identified districts 13, 14, 15, 16, 17, and 18 in Shiraz's core as having the highest potential for multi-story parking facilities among the 30 central districts. Additionally, the findings showed that accessibility to major roads, population density, and proximity to trip generators were the most relevant factors in deciding where parking facilities should be located in Shiraz. Policymakers and urban planners can use the insights provided by the outcomes of these models to make well-informed decisions on parking infrastructure expenditures.